E-Books interativos sobre objetos de aprendizagem do Scratch para docentes que ensinam matemática nos Anos Iniciais. - Gonçalves, Ana Karen (2024)
he use of digital technologies in Education is a requirement that requires the training of teachers and the adaptation of the school environment. Self-training is a process that runs through the entire teaching career and involves teachers' reflection on their pedagogical practices, analysis of needs and the search for training and knowledge that translates into changes in their practices and new analysis. The use of Scratch learning objects can be an alternative to integrate digital technologies in the teaching of mathematics and contribute to the development of students' skills and Mathematical Thematic Units described in the Common National Curricular Base for the Early Years. As part of the search for an answer to the research question: How do self-training teachers of the Early Years evaluate the use of interactive e-books on Scratch learning objects in the mathematics classroom? we developed a collection of six interactive e books created as learning objects to guide teachers in self-training how to use these objects. The research was qualitative and application-oriented and aimed to explicitly represent educators' understanding of a collection of interactive e-books that guide the use of the Scratch repository in mathematics classrooms from a self-training perspective. To this end, the interactive e-books were made available to volunteers who teach early childhood math so that they could use them, become familiar with the Scratch learning objects and, after reflecting on the relationship with their pedagogical practices, assess the possibility of integrating them into their lesson plans. They were then asked to complete an evaluation questionnaire about their use of the collection, their knowledge acquisition, their reflections and their pedagogical practices. The data reflected reports of possible knowledge acquisition by the teachers and changes in their pedagogical practices. After analysis, four categories were identified: (C1) Barriers to implementation, (C2) Opportunities for reflection and change in professional practice, (C3) Necessary organizational elements, and (C4) Characteristics of the educational resource. Evidence of self-training was observed in the use of interactive e-books, as well as in the diversity of training among participants who used the same material, showing the importance of self-training reflection on the personal and professional reality of each individual.